Analisis Kelayakan Bisnis Menggunakan Business Model Canvas Dalam Upaya Pengembangan Usaha - Hardiansyah, Sigit; Lulus Setiawan, Wawan; Kharisma Genta, Franklin (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Supersub Apparel was founded in early 2021 by two students from different universities. Previously, in 2018, they established a similar business that temporarily ceased operations due to issues, before restarting in 2021. Supersub Apparel is one of the SMEs engaged in sports jersey production services. In this context, to sustain and maintain the existence of Supersub Apparel, it requires the implementation of business development strategies such as Business Model Canvas (BMC) and Business Feasibility Study. The objective of this research is to assess the implementation of BMC at Supersub Apparel in Bekasi Regency and evaluate its feasibility from the aspects of market and marketing, technical/operational, and financial aspects. The method used in this study is a case study, where data were obtained through interviews, observations, literature studies, and analyzed descriptively. By using BMC and Business Feasibility Study tools, the authors could identify and improve the necessary indicators for Supersub Apparel in its business development. The research findings indicate that Supersub Apparel has effectively implemented Business Model Canvas with clear target markets and good cooperation with suppliers. From the business feasibility analysis, the market and marketing aspects show promising prospects, while the technical/operational aspects are deemed feasible with easy access to raw materials and production services. Financially, the analysis shows that Supersub Apparel is viable with a Payback Period (PP) of approximately 4 months and a Profitability Index (PI) of 1.54.